Inclusive Education in the diversifying environments of Finland, Iceland, and the Netherlands : A multilingual systematic review - Wolff, Charlotte E.; Huilla, Heidi; Tzaninis, Yannis; Magnúsdóttir, Berglind Rós; Lappalainen, Sirpa; Paulle, Bowen; Seppänen, Piia; Kosunen, Sonja (Research in Comparative and International Education, 2021)
This review investigates how the scholarly fields, themes and concepts of 'inclusive education' are applied in the research and educational contexts of Finland, Iceland and the Netherlands. It identifies and outlines which thematic areas of research and sub-fields of study are referenced in each country by applying a systematic, multilingual approach. We reviewed literature in the local languages of each of these countries over the past decade, from 2007 to 2018, paying particular attention to (a) micro-level, in-depth, classroom interactions; (b) social and political contexts; and (c) social categories. Results of this review emphasise that across all three countries (a) there are similar conceptualisations of inclusive education dominated by categories of disability and special needs, and (b) there is a similar lack of attention to modes of exclusion based on social class, gender, ethnicity and geography as well as to how these can be addressed by more advanced research on inclusive education in these local spheres. Peer reviewed